Fusion polypeptide and PCL (polycaprolactone) stent material with antibacterial and anticoagulant dual-functional coating

By fusing peptides and dopamine on the surface of PCL scaffold material, the dual functions of antibacterial and anticoagulant are achieved, solving the problem that existing vascular scaffold materials are prone to thrombosis and bacterial infection in small-diameter artificial vascular reconstruction, and significantly improving the biological of the material Mechanical properties and compatibility.

CN119390849AActive Publication Date: 2025-02-07SOUTH CHINA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411494331.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing vascular stent materials are prone to complications such as thrombosis and bacterial infection in small-diameter artificial vascular reconstruction, which limits its application in surgical treatment of cardiovascular diseases.

Method used

Using fusion polypeptide and PCL scaffold material with antibacterial and anticoagulant dual-function coatings, PCL scaffolds are prepared by electrospinning technology, and dopamine and fusion polypeptides are loaded on its surface to achieve efficient anticoagulant and antibacterial.

Benefits of technology

The antibacterial and anticoagulant properties of vascular stent materials are significantly improved, their biomechanical properties and compatibility in small-diameter vascular reconstruction are enhanced, and the risk of thrombosis and bacterial infection is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390849A_ABST
    Figure CN119390849A_ABST
Patent Text Reader

Abstract

The invention discloses a fusion polypeptide and a PCL (polycaprolactone) stent material with an antibacterial and anticoagulant dual-functional coating. The PCL stent material with the antibacterial and anticoagulant dual-functional coating comprises a PCL fiber stent, a dopamine coating and a fusion polypeptide coating, the dopamine coating is arranged on the surface of the PCL fiber scaffold, and the fusion polypeptide coating is arranged on the surface of the dopamine coating. Dopamine is loaded on the surface of the PCL fiber scaffold, and a fusion polypeptide containing a hirudin sequence and an antibacterial polypeptide HHC36 sequence is fixed on the surface by utilizing a condensation reaction between amino and carboxyl, so that the scaffold material can stably prevent thrombus and resist bacteria for a long time. The method is simple and feasible in process and good in repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of degradable vascular stents, and in particular to a fusion polypeptide and a PCL stent material with an antibacterial and anticoagulant dual-functional coating. Background Art

[0002] Cardiovascular disease (CVD) poses a serious threat to human health. So far, there are many methods for treating CVD, but coronary artery bypass surgery is still recognized as the most effective treatment. At present, the main source of vascular grafts is the patient's own great saphenous vein. Although autologous vascular grafts have good biocompatibility, non-immune response, non-toxicity and easy growth, the patient's individual donor tissue is often insufficient to meet clinical needs. Therefore, artificial blood vessels replacing autologous blood vessels are the best choice for the treatment of CVD and have potential application prospects. Unfortunately, synthetic grafts still face many challenges that we need to overcome, such as susceptibility to thrombosis, bacterial infection and other complications. It is these shortcomings that restrict the development of small-diameter (inner diameter <6mm) vascular grafts. Therefore, it is urgent to develop an artificial vascular graft with strong biomechanical properties, good compatibility, implantability, and suitable for small-diameter vascular reconstruction, which will have a huge impact on the surgical treatment of cardiovascular diseases. Therefore, this study aims to prepare a nanofiber vascular scaffold material with good mechanical properties, so that it has both anticoagulation and antibacterial functions, and lay a theoretical foundation for small-diameter artificial vascular stents.

[0003] Hirudin is a strong thrombin inhibitor that can irreversibly bind thrombin at a 1:1 molar ratio to form a non-covalent complex, thereby preventing a series of thrombin-mediated coagulation reactions. Hirudin can effectively inhibit thrombin activity without any auxiliary factors. Moreover, hirudin can inhibit the fibrin binding site of thrombin, which can not only inhibit free thrombin, but also inhibit thrombin bound to blood clots.

[0004] As a new type of antibacterial material, antimicrobial peptides (AMPs) have a very wide source, but most antimicrobial peptides contain only 9-50 amino acids, and the molecular weight is generally below 10kDa, with the advantages of broad-spectrum antibacterial properties and low drug resistance. Since antimicrobial peptides have different amino acid sequences and spatial conformations, there is still no consensus on the antibacterial mechanism of antimicrobial peptides. The most recognized hypothesis is that antimicrobial peptides act on the bacterial membrane, destroying its integrity, causing osmotic imbalance inside and outside the membrane, outflow of contents, and ultimately leading to bacterial apoptosis. In addition, antimicrobial peptides have good biocompatibility and broad-spectrum bactericidal ability, and can kill clinically relevant Gram-positive and Gram-negative bacteria. And its components will not cause rapid mutation of drug-resistant bacteria, so it can be used as an ideal drug for local sustained release.

[0005] However, current hirudin and antibacterial peptides still have the problem of low anticoagulant and antibacterial properties. The development of high-performance anticoagulant and antibacterial materials has broad application prospects. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a fusion polypeptide and a PCL scaffold material with an antibacterial and anticoagulant dual-functional coating, which can achieve sustainable and efficient anticoagulation and antibacterial effects on the basis of meeting the requirements of general tissue engineering scaffolds.

[0007] The purpose of the present invention is achieved by at least one of the following technical solutions.

[0008] The present invention provides a fusion polypeptide, the structural formula of which is as follows:

[0009]

[0010] The present invention provides a PCL stent material with an antibacterial and anticoagulant dual-functional coating, comprising a PCL fiber stent, a dopamine coating, and a fusion polypeptide coating; the dopamine coating is on the surface of the PCL fiber stent, the fusion polypeptide coating is on the surface of the dopamine coating, and the fusion polypeptide is the above-mentioned fusion polypeptide.

[0011] Preferably, the fusion polypeptide forms a coating on the surface of the dopamine coating after carboxyl activation.

[0012] The PCL scaffold material capable of antibacterial and anticoagulant provided by the present invention is composed of a polycaprolactone scaffold, dopamine and a fusion polypeptide (HH). The PCL scaffold is prepared by electrospinning technology, and the deposited dopamine is grafted onto the fusion polypeptide (HH), so that the surface of the scaffold can be stably and efficiently anticoagulant and antibacterial for a long time.

[0013] The present invention provides a method for preparing the above-mentioned PCL stent material having an antibacterial and anticoagulant dual-functional coating, comprising the following steps:

[0014] (1) soaking the PCL fiber scaffold in a dopamine solution and placing it in a dark place, taking it out, washing and drying it to obtain a PCL-PDA nanofiber scaffold;

[0015] (2) dissolving the fusion polypeptide in water, and adding WSC and NHS to prepare a fusion polypeptide solution;

[0016] (3) Immersing the PCL-PDA nanofiber scaffold material in the fusion polypeptide solution of step (2), reacting, taking out, washing, and drying to obtain a PCL scaffold material having an antibacterial and anticoagulant dual-functional coating.

[0017] Preferably, in step (1), the concentration of the dopamine solution is 1-3 mg / ml, and the pH value of the dopamine solution is 8-9;

[0018] Further preferably, the pH value of the dopamine solution in step (1) is 8.5, and the pH value of the dopamine solution can be adjusted using a tris buffer.

[0019] Further preferably, the concentration of the dopamine solution in step (1) is 2 mg / mL.

[0020] Preferably, in step (1), the time for standing and avoiding light treatment is 12-36 hours.

[0021] More preferably, the time for standing and avoiding light treatment in step (1) is 24 hours.

[0022] Preferably, in step (2), the concentration of the fusion polypeptide in the fusion polypeptide solution is 0.5-2 mg / ml.

[0023] Further preferably, the concentration of the fusion polypeptide in the fusion polypeptide solution in step (2) is 1 mg / mL.

[0024] Preferably, in step (2), the solubility of WSC in the fusion polypeptide solution is 10-100 mM, and the solubility of NHS in the fusion polypeptide solution is 5-50 mM.

[0025] Further preferably, in step (2), the solubility of WSC in the fusion polypeptide solution is 50 mM, and the solubility of NHS in the fusion polypeptide solution is 20 mM.

[0026] Preferably, the water in step (2) is ultrapure water.

[0027] Preferably, in step (3), the reaction time is 1-48 hours.

[0028] More preferably, the reaction time in step (3) is 24 hours.

[0029] Preferably, steps (1), (2) and (3) are performed at room temperature.

[0030] The present invention provides the use of the above-mentioned fusion polypeptide or the above-mentioned PCL stent material with antibacterial and anticoagulant dual-functional coating in the preparation of antibacterial and / or anticoagulant materials.

[0031] The present invention provides a method for preparing a PCL stent material with an antibacterial and anticoagulant dual-functional coating, wherein a PCL stent is prepared by electrospinning technology, dopamine is loaded on its surface, and an HH fusion polypeptide is constructed on the stent surface through a condensation reaction between amino groups and carboxyl groups.

[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0033] The present invention provides an antibacterial and anticoagulant vascular stent material. The hirudin sequence in the fusion polypeptide can promote endothelial cell adhesion and proliferation and has anticoagulant properties. The antibacterial polypeptide sequence in the fusion polypeptide can effectively prevent bacterial infection of related materials. After the hirudin sequence and the antibacterial polypeptide sequence are fused and constructed on the surface of the material, the antibacterial and anticoagulant properties are significantly improved compared to the corresponding mixed polypeptide. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscopy image of the PCL scaffold.

[0035] Figure 2 It is a fusion polypeptide structure based on hirudin and HHC36.

[0036] Figure 3 The antibacterial effects of different stents in Example 1 on different bacteria.

[0037] Figure 4 The number of platelets on the surface of different stent materials in Example 1. DETAILED DESCRIPTION

[0038] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0039] The PCL scaffold preparation method is as follows:

[0040] Dissolve PCL in hexafluoroisopropanol with a concentration of 0.1g / ml. Stir at room temperature for 12h to completely dissolve PCL in hexafluoroisopropanol. Use a syringe to absorb the evenly mixed spinning solution for use. Cut the aluminum foil of appropriate size and stick it flat on the receiving roller of the electrospinning machine with transparent tape. Place the syringe upright for a while and exhaust the air above. Then remove the needle of the syringe and connect it to a polyethylene catheter. The other end of the catheter is connected to a 21G spinning needle. After fixing the whole on the spinning machine, set the spinning-related parameters: flow rate of 1ml / h, spinning solution voltage of 14KV, receiving distance of 15cm, temperature of 25-30℃, humidity of 40-50%, and roller speed of 80rpm. Start the power supply, injection pump and roller collector program, and the generated nanofibers are collected on the roller. After spinning, the sample is placed in a vacuum drying oven for 12h to remove the residual hexafluoroisopropanol organic solvent. The average diameter of the PCL fiber scaffold is 460nm (morphology as shown in Figure 1 shown).

[0041] The test method for antibacterial performance is as follows:

[0042] The bacteria were prepared at a concentration of 10 7 CFU / mL suspension, 30 μL was added to the scaffold and cultured at 37°C for 2 hours. After that, the scaffold with bacteria was immersed in 1 mL PBS buffer, ultrasonicated for 1 minute and vortexed for 1 minute to free the bacteria adhering to the surface of the material. The PBS solution was collected, applied to the agar plate after gradient dilution, and cultured at 37°C for 24 hours, and then the colonies were counted and the antibacterial rate was calculated. The scaffold without polypeptide functionalization was used as the blank group, and the scaffold with mixed polypeptide functionalization was used as the control group.

[0043] The test method for anticoagulant performance is as follows:

[0044] Take 30 μL of platelet-rich plasma, add it to the stent, and incubate it at 37°C for 2 hours. After that, wash the stent with PBS solution, and use FITC solution to stain the platelets adhering to the surface of the material. Observe under an upright fluorescence microscope, count the platelets adhering to the surface of the material, and calculate the reduction rate of platelet adhesion. The stent without polypeptide functionalization was used as the blank group, and the stent with mixed polypeptide functionalization was used as the control group.

[0045] The fusion peptide based on hirudin and HHC36 is synthesized by solid phase synthesis, and its structural formula is as follows Figure 2 As shown, each amino acid is added to the peptide synthesizer in sequence to perform a condensation reaction between the amino group and the carboxyl group.

[0046] Example 1

[0047] (1) 1×1×0.1cm 3 The PCL fiber scaffold was immersed in 1 mL of a 2 mg / mL dopamine solution, the pH was adjusted to 8.5, and the scaffold was kept in a dark place for 24 hours, then taken out, washed, and dried to obtain a PCL-PDA nanofiber scaffold;

[0048] (2) preparing a solution of 1 mg / mL of the fusion polypeptide HH, and adding 50 mM WSC and 20 mM NHS;

[0049] A mixed peptide solution was prepared, wherein the concentrations of the hirudin sequence peptide and the HHC36 peptide were both 1 mg / mL, and 50 mM WSC and 20 mM NHS were added;

[0050] (3) The PCL-PDA scaffold materials were immersed in 1 mL of the solution described in step (2) respectively, and after standing for reaction for 24 hours, they were taken out, washed, and dried to obtain PCL-PDA-HH scaffold (fusion polypeptide scaffold) and PCL-PDA-mix (mixed polypeptide scaffold).

[0051] The blank scaffold (PCL scaffold without modification), the obtained PCL-PDA-HH scaffold and PCL-PDA-mix were tested for antibacterial and anticoagulant properties.

[0052] Compared with the blank scaffold material, the antibacterial rates of the PCL-PDA-HH scaffold material against Staphylococcus aureus and Escherichia coli within 2 hours were 99.96% and 99.89%, respectively, and the antibacterial rates of the PCL-PDA-mix scaffold material against Staphylococcus aureus and Escherichia coli within 2 hours were 53.2% and 56.8%, respectively;

[0053] Compared with the blank scaffold material, the number of platelet adhesion in the PCL-PDA-HH scaffold material was reduced by 95% within 2 hours, and the number of platelet adhesion in the PCL-PDA-mix scaffold material was reduced by 32% within 2 hours.

[0054] This case is the best example, and the results are shown in Figure 3 , Figure 4 .

[0055] Example 2

[0056] (1) 1×1×0.1cm 3 The PCL fiber scaffold was immersed in 1 mL of a 1 mg / mL dopamine solution, the pH was adjusted to 8, and the scaffold was kept in a dark place for 12 hours, and then washed and dried to obtain a PCL-PDA nanofiber scaffold.

[0057] (2) preparing a solution of fusion polypeptide HH at a concentration of 0.5 mg / mL, and adding 10 mM WSC and 5 mM NHS;

[0058] A mixed polypeptide solution was prepared, wherein the concentrations of the hirudin sequence polypeptide and the HHC36 polypeptide were both 0.5 mg / mL, and 10 mM WSC and 5 mM NHS were added;

[0059] (3) The PCL-PDA scaffold materials were immersed in 1 mL of the solution described in step (2) respectively, and after standing for reaction for 24 hours, they were taken out, washed, and dried to obtain PCL-PDA-HH scaffold (fusion polypeptide scaffold) and PCL-PDA-mix (mixed polypeptide scaffold).

[0060] The blank scaffold, the obtained PCL-PDA-HH scaffold and PCL-PDA-mix were tested for antibacterial and anticoagulant properties.

[0061] Compared with the blank scaffold material, the antibacterial rates of the PCL-PDA-HH scaffold material against Staphylococcus aureus and Escherichia coli within 2 hours were 32.1% and 22.8%, respectively, and the antibacterial rates of the PCL-PDA-mix scaffold material against Staphylococcus aureus and Escherichia coli within 2 hours were 5.8% and 12.9%, respectively;

[0062] Compared with the blank scaffold material, the number of platelet adhesion in the PCL-PDA-HH scaffold material was reduced by 5% within 2 hours, and the number of platelet adhesion in the PCL-PDA-mix scaffold material was reduced by 1% within 2 hours.

[0063] Example 3

[0064] (1) 1×1×0.1cm 3 The PCL fiber scaffold was immersed in 1 mL of a 3 mg / mL dopamine solution, the pH was adjusted to 9, and the scaffold was kept in the dark for 36 hours, and then washed and dried to obtain a PCL-PDA nanofiber scaffold.

[0065] (2) preparing a solution of fusion polypeptide HH at a concentration of 2 mg / mL, and adding 100 mM WSC and 50 mM NHS;

[0066] A mixed peptide solution was prepared, wherein the concentrations of the hirudin sequence peptide and the HHC36 peptide were both 2 mg / mL, and 100 mM WSC and 50 mM NHS were added;

[0067] (3) The PCL-PDA scaffold materials were immersed in 1 mL of the solution described in step (2) respectively, and after standing for reaction for 48 hours, they were taken out, washed, and dried to obtain PCL-PDA-HH scaffold (fusion polypeptide scaffold) and PCL-PDA-mix (mixed polypeptide scaffold).

[0068] The blank scaffold, the obtained PCL-PDA-HH scaffold and PCL-PDA-mix were tested for antibacterial and anticoagulant properties.

[0069] Compared with the blank scaffold material, the antibacterial rates of the PCL-PDA-HH scaffold material against Staphylococcus aureus and Escherichia coli within 2 hours were 90.1% and 98.2%, respectively, and the antibacterial rates of the PCL-PDA-mix scaffold material against Staphylococcus aureus and Escherichia coli within 2 hours were 55.1% and 32.8%, respectively;

[0070] Compared with the blank scaffold material, the number of platelet adhesion in the PCL-PDA-HH scaffold material was reduced by 89% within 2 hours, and the number of platelet adhesion in the PCL-PDA-mix scaffold material was reduced by 16% within 2 hours.

[0071] Example 4

[0072] (1) 1×1×0.1cm 3 The PCL fiber scaffold was immersed in 1 mL of a 3 mg / mL dopamine solution, the pH was adjusted to 8.5, and the scaffold was kept in a dark place for 30 hours, and then washed and dried to obtain a PCL-PDA nanofiber scaffold.

[0073] (2) preparing a solution of fusion polypeptide HH at a concentration of 1.5 mg / mL, and adding 20 mM WSC and 20 mM NHS;

[0074] A mixed peptide solution was prepared, wherein the concentrations of the hirudin sequence peptide and the HHC36 peptide were both 1.5 mg / mL, and 20 mM WSC and 20 mM NHS were added;

[0075] (3) The PCL-PDA scaffold materials were immersed in 1 mL of the solution described in step (2) respectively, and after standing for reaction for 36 hours, they were taken out, washed, and dried to obtain PCL-PDA-HH scaffold (fusion polypeptide scaffold) and PCL-PDA-mix (mixed polypeptide scaffold).

[0076] The blank scaffold, the obtained PCL-PDA-HH scaffold and PCL-PDA-mix were tested for antibacterial and anticoagulant properties.

[0077] Compared with the blank scaffold material, the antibacterial rates of the PCL-PDA-HH scaffold material against Staphylococcus aureus and Escherichia coli within 2 hours were 84.2% and 86.1%, respectively, and the antibacterial rates of the PCL-PDA-mix scaffold material against Staphylococcus aureus and Escherichia coli within 2 hours were 33.8% and 25.1%, respectively;

[0078] Compared with the blank scaffold material, the number of platelet adhesion in the PCL-PDA-HH scaffold material was reduced by 75% within 2 hours, and the number of platelet adhesion in the PCL-PDA-mix scaffold material was reduced by 12% within 2 hours.

[0079] Example 5

[0080] (1) 1×1×0.1cm 3 The PCL fiber scaffold was immersed in 1 mL of a 2.5 mg / mL dopamine solution, the pH was adjusted to 8, and the scaffold was kept in a dark place for 20 hours, and then washed and dried to obtain a PCL-PDA nanofiber scaffold.

[0081] (2) preparing a solution of fusion polypeptide HH at a concentration of 1.0 mg / mL, and adding 35 mM WSC and 15 mM NHS;

[0082] A mixed polypeptide solution was prepared, wherein the concentrations of the hirudin sequence polypeptide and the HHC36 polypeptide were both 1.0 mg / mL, and 35 mM WSC and 15 mM NHS were added;

[0083] (3) The PCL-PDA scaffold materials were immersed in 1 mL of the solution described in step (2) respectively, and after standing for reaction for 24 hours, they were taken out, washed, and dried to obtain PCL-PDA-HH scaffold (fusion polypeptide scaffold) and PCL-PDA-mix (mixed polypeptide scaffold).

[0084] The blank scaffold, the obtained PCL-PDA-HH scaffold and PCL-PDA-mix were tested for antibacterial and anticoagulant properties.

[0085] Compared with the blank scaffold material, the antibacterial rates of the PCL-PDA-HH scaffold material against Staphylococcus aureus and Escherichia coli within 2 hours were 70.1% and 75.6%, respectively, and the antibacterial rates of the PCL-PDA-mix scaffold material against Staphylococcus aureus and Escherichia coli within 2 hours were 22.6% and 13.8%, respectively;

[0086] Compared with the blank scaffold material, the number of platelet adhesion in the PCL-PDA-HH scaffold material was reduced by 76% within 2 hours, and the number of platelet adhesion in the PCL-PDA-mix scaffold material was reduced by 11% within 2 hours.

Claims

1. A fusion polypeptide, characterized in that: The structural formula is as follows:

2. A PCL stent material with an antibacterial and anticoagulant dual-functional coating, characterized in that: It comprises a PCL fiber scaffold, a dopamine coating and a fusion polypeptide coating; the dopamine coating is on the surface of the PCL fiber scaffold, the fusion polypeptide coating is on the surface of the dopamine coating, and the fusion polypeptide is the fusion polypeptide described in claim 1.

3. The PCL stent material with antibacterial and anticoagulant dual-function coating according to claim 2, characterized in that: The fusion polypeptide forms a coating on the surface of the dopamine coating after being activated by the carboxyl group.

4. The method for preparing the PCL stent material with antibacterial and anticoagulant dual-functional coating according to any one of claims 2 to 3, characterized in that: The steps include: (1) soaking the PCL fiber scaffold in a dopamine solution and placing it in a dark place, taking it out, washing and drying it to obtain a PCL-PDA nanofiber scaffold; (2) dissolving the fusion polypeptide in water, and adding WSC and NHS to prepare a fusion polypeptide solution; (3) Immersing the PCL-PDA nanofiber scaffold material in the fusion polypeptide solution of step (2), reacting, taking out, washing, and drying to obtain a PCL scaffold material having an antibacterial and anticoagulant dual-functional coating.

5. The preparation method according to claim 4, characterized in that: In step (1), the concentration of the dopamine solution is 1-3 mg / ml, and the pH value of the dopamine solution is 8-9.

6. The preparation method according to claim 4, characterized in that: In step (1), the time for standing and avoiding light treatment is 12-36 hours.

7. The preparation method according to claim 4, characterized in that: In step (2), the concentration of the fusion polypeptide in the fusion polypeptide solution is 0.5-2 mg / ml.

8. The preparation method according to claim 4, characterized in that: In step (2), the solubility of WSC in the fusion polypeptide solution is 10-100 mM, and the solubility of NHS in the fusion polypeptide solution is 5-50 mM.

9. The preparation method according to claim 1, characterized in that: In step (3), the reaction time is 1-48 hours.

10. Use of the fusion polypeptide according to claim 1 or the PCL scaffold material with an antibacterial and anticoagulant dual-functional coating according to any one of claims 2 to 3 in the preparation of antibacterial and / or anticoagulant materials.

Citation Information

Patent Citations

  • Target multifunctional anti-embolism fusion protein as well as preparation method and application thereof

    CN102180973A

  • Chemotactic antibacterial nanometer material, and preparation method and application thereof

    CN111529682A

  • Reservoir type hirudin fusion protein and application thereof

    CN117534771A

  • Bifunctional fusion proteins formed from hirudin and TAP

    US20020173620A1